Optical and structural properties of tungsten-doped barium strontium titanate. (2020) - Kavitha, V.; Mahalingam, P.; Jeyanthinath, M.; Sethupathi, N.
Abstract: The effect of variation in the tungsten content on the tungsten doped barium strontium titanate for their use in DSSC is studied. Samples were prepared by solid state reaction for the dopant variation of x = 0, 0.2, 0.4 and 0.6. The characterization of optical properties was performed by UV–Vis spectrometer by diffused reflectance Method to find the optical band gab and microstructural characterization was performed by X-ray diffraction (XRD) and the FESEM reveals the morphology of the samples prepared. Tungsten doped barium strontium titanate shows good variation in the morphology and the structure.